Intelligence and state surveillance in modern societies : an international perspective - Lemieux, Frederic (Emerald Publishing Limited, 2024)
Building on Frederic Lemieux's previous work exploring how Western state surveillance and intelligence activities have drastically adapted to new domestic and global challenges, this second edition expands on additional dimensions of intelligence and surveillance activities conducted in modern societies. Featuring new chapters on inter-agency cooperation at both national and international levels, cyber intelligence (CI), the link between intelligence and police cooperation, the Drug Enforcement Administration (DEA), and international operations, counterterrorism, and intelligence activities conducted by the United States since September 11, 2001, Lemieux also includes several updates to existing chapters, including the role of AI in intelligence analysis. Delving into how counterterrorism operations have profoundly changed how intelligence activities are conducted by integrating new technologies, new partnerships, and raising new ethical dilemmas, the author also expands on the intelligence operations undertaken in cyberspace to describe the emerging cyber intelligence field. Offering a compelling understanding of contemporary state surveillance dynamics, this second edition is a timely update that lands at the critical intersection of cutting-edge technology and international security.